Identifikasi Senyawa Flavonoid dalam Fase n-Butanol dari Ekstrak Metanol Daun Wungu (Graptophyllum pictum (L.) Griff) - Zuhelmi Aziz; Wiwi Winarti; Kona Nate (JURNAL ILMU KEFARMASIAN INDONESIA, 2006)
Wungu leaves is one of the herbal plants in Indonesia that have been used significantly by the society to cure scare, swollen, ulcer, gall stone, abscess, skin diseases, liver, hearing disfunction, hemorrhoids, bloody cough, fever and laxative, isolation and identification of the type of flavonoid substance found in n-butanol phase of Wungu leaves methanol extract have been conducted by employing identification by UV-visible spectrophotometry, the result of the examination showed that isolate NB-IV was presumably considered as flavonol substance with 3-OH (with or without 5-OH), isolate NB-V was presumably considered as antosianidin substance with o-diOH on ring A, isolate NB-VI and isolate NBVII was presumably considered as flavonol substance with OH on position 3,5,7 and o-diOH on ring B.